Improving Indonesian EFL Learners’ Motivation Through Computer Assisted Learning (CALL) - Reza Anggriyashati Adara; Aridhotul Haqiyah (Journal of English Language Studies, 2021)
It has been argued that technology can improve learners’ motivation. Furthermore, technology integration has been regarded one of motivational strategies or techniques to improve learners’ positive attitudes. In this regard, one of motivational strategies that can be given to learners is incorporating CALL (Computer Assisted Language Learning) to EFL (English as a Foreign Language) classrooms. Therefore, the present research analysed the effects of CALL on a group of Indonesian EFL learners’ motivation. In order to obtain the results, the present research conducted a quasi-experimental study toward 40 college students. In addition, a set of questionnaires adapted from Taguchi, Magid, & Papi (2009) as well as semi-structured interviews were used as research instruments. In addition, English tests will be given to the respondents to see the effects of CALL on the improvement of learners’ achievements. The results of present study suggest the positive effects of CALL on learners’ motivation. In addition, learners’ achievement also improved after being intervened with CALL. Nevertheless, the use of CALL needs to be supported by teachers who are capable enough to provide suitable materials that suit learners’ need. Thus, it seems important for teachers to be provided with prior sufficient training on how to use CALL effectively.